Strategi penguatan literasi lingkungan melalui budaya sekolah di Sekolah Dasar - Akmalia, Veny Kusuma; Nawangsih, Rulita Dyah; Wardani, Kristi; Cahyandaru, Pramudya (Kuras Institute, 2023)
This paper explains the implementation of environmental literacy in elementary schools and explores strategies to strengthen environmental literacy through school culture. The research was conducted using qualitative descriptive research methods, and the data collection techniques used were interviews, observation, and documentation. The research was conducted at SD N Keputran 1, and the research courses included one principal, two teachers, and two fourth grade students. This paper highlights the activities that have been pursued in implementing environmental literacy in schools, including routine habituation, example, and learning through positive habits of school culture. This paper also discusses the obstacles faced by schools in implementing environmental literacy and strategies developed by schools to strengthen environmental literacy, such as developing school policies, developing education-based curricula, developing participatory-based activities, and managing or developing school support facilities.